THE ABILITY OF Bacillus sp. BACTERIA FROM THE ROKAN RIVER ESTUARINE WATERS TO DEGRADE MICROPLASTICS - Andini Nurhidayah; Nursyirwani Nursyirwani; Feli Feliatra (Asian Journal of Aquatic Sciences, 2026)
Microplastic pollution in aquatic environments has emerged as a critical global environmental concern. Its presence has been widely detected in various environmental compartments, including estuaries. The objective of this study was to assess the ability of Bacillus sp. isolated from the Rokan River estuary waters to degrade microplastics, namely polystyrene (PS), polyethylene (PE), and polypropylene (PP), and to observe changes in their surface morphology using Scanning Electron Microscopy (SEM). The method used was a one-factor Completely Randomized Design (CRD) experiment with three replications. The degradation test was conducted gravimetrically over 60 days of incubation. The results showed that the highest average degradation rate was found in PE (4.09%), followed by PS (1.86%) and PP (1.19%). The Kruskal-Wallis statistical test yielded a p-value of 0.361 (p > 0.05), indicating no significant difference among the plastic types. SEM analysis confirmed morphological changes, including cracks, pores, and holes, on the surfaces of the treated plastics. The highest average bacterial count was found in the PE treatment (20.8 x 10¹⁰ CFU/mL), followed by PS (18.8 x 10¹⁰ CFU/mL) and PP (13.5 x 10¹⁰ CFU/mL). Therefore, it is concluded that Bacillus sp. has potential as an early indicator of microplastic biodegradation, although the degradation rate remains relatively low